1988
DOI: 10.1159/000248533
|View full text |Cite
|
Sign up to set email alerts
|

Nuchal Nevus flammeus as a Skin Marker of Prognosis in Alopecia areata

Abstract: In this work, the incidence of nuchal nevus flammeus was studied in 205 patients suffering from various forms of alopecia areata, as well as in a group of 555 volunteers without alopecia areata xamined in our outpatient clinic. The incidence of nuchal nevus flammeus in the totalis-universalis form of alopecia areata was 58.2% (examined patients, n = 79), in ophiasis-extensive forms 22.8% (examined patients, n = 70) and in simple forms of alopecia areata 3.6% (examined patients, n = 56). In the group of 555 vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 2 publications
1
10
0
4
Order By: Relevance
“…Studies showed that the prevalence of nuchal nevus flammeus (NNF) was significantly increased in patients with AA, especially severer forms [10,11,12]. We also conducted a study to investigate whether AA is associated with NNF.…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the prevalence of nuchal nevus flammeus (NNF) was significantly increased in patients with AA, especially severer forms [10,11,12]. We also conducted a study to investigate whether AA is associated with NNF.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırmamızın sonuçları, uzun hastalık süresinin kötü prognoz göstergesi olduğunu destekler niteliktedir. Nevus flammeus AA'lı hastalarda sıktır ve kötü prognozu gösterir 5,20 . Araştırmamızda %14,9 oranında saptanan nevus flammeus, şiddetli tutulum gösteren olgularda yüksek (p=0,017) bulundu.…”
Section: Discussionunclassified
“…Alopesi areatanın patogenezi tam olarak bilinmemekte ise de günümüzdeki baskın görüş, genetik yatkınlığı olan bireylerde, çevresel tetikleyicilerle kıl foliküllerine karşı gelişen organ spesifik otoimmün bir hastalık olduğu yönündedir 1,2 . Bu çalışmada polikliniğimize başvuran AA'lı hastaların, klinik ve demografik özellikleri ile hastalık seyrindeki kötü prognostik faktörleri incelenerek, AA'nın Türkiye'deki epidemiyolojik özelliklerinin tanınmasına katkı amaçlandı 1,4,5 .…”
Section: Introductionunclassified
“…Ense yerleşimli nevüs flammeus ile ilgili birkaç çalışma yapılmıştır ve daha dirençli ve ciddi AA tipleri için belirteç olabileceği öne sürülmüştür (20)(21)(22). Oğuz ve ark.…”
Section: Discussionunclassified